2016
DOI: 10.1177/0022034516663465
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cavity Disinfectant Containing Antibacterial Monomer MDPB

Abstract: An experimental cavity disinfectant (ACC) that is intended to be used for various direct and indirect restorations was prepared by adding an antibacterial monomer 12-methacryloyloxydodecylpyridinum bromide (MDPB) at 5% into 80% ethanol. The antibacterial effectiveness of ACC and its influences on the bonding abilities of resin cements were investigated. To examine the antibacterial activity of unpolymerized MDPB, the minimum inhibitory and bactericidal concentrations (MIC and MBC) were determined for Streptoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Previous studies incorporated QAMs into dental materials because they reduced the biofilm growth and viability [11,15,16,[25][26][27]. Novel dental materials with 12-methacryloyloxydodecylpyridinium bromide (MDPB), methacryloxylethyl cetyl dimethyl ammonium chloride (DMAE-CB), and cetylpyridinium chloride (CPC), as well as other compositions, effectively hindered bacteria and biofilm growth [28][29][30][31][32][33][34]. The antibacterial potency increased with increasing the alkyl chain length (CL) from 3 to 16, with DMAHDM having CL of 16 showing the strongest bactericidal potency [34].…”
Section: Antibacterial and Protein-repellent Orthodontic Cement To Inmentioning
confidence: 99%
“…Previous studies incorporated QAMs into dental materials because they reduced the biofilm growth and viability [11,15,16,[25][26][27]. Novel dental materials with 12-methacryloyloxydodecylpyridinium bromide (MDPB), methacryloxylethyl cetyl dimethyl ammonium chloride (DMAE-CB), and cetylpyridinium chloride (CPC), as well as other compositions, effectively hindered bacteria and biofilm growth [28][29][30][31][32][33][34]. The antibacterial potency increased with increasing the alkyl chain length (CL) from 3 to 16, with DMAHDM having CL of 16 showing the strongest bactericidal potency [34].…”
Section: Antibacterial and Protein-repellent Orthodontic Cement To Inmentioning
confidence: 99%
“…: -implants 97) , pulp capping materials 98) , Transbond XT 99) , pit and fissure sealing 100) , cavity disinfectant 101) , resin cement 102), zinc phosphate cement, and zinc polycarboxylate cement 103) . These studies have shown that QACs possess antimicrobial activities against bacteria and fungi including S. mutans, L. acidophilus, C. albicans, E. faecalis ect.…”
Section: Discussionmentioning
confidence: 99%
“…Agar disc diffusion tests were performed as previously reported 11) . Briefly, S. mutans strain NCTC10449 was used and cultivated in Brain Heart Infusion (BHI; Becton Dickinson, Sparks, MD, USA) broth at 37°C.…”
Section: Agar Disc Diffusion Testsmentioning
confidence: 99%
“…MIC and MBC of Primer, NaOCl, and Primer/NaOCl as prepared above against S. mutans were determined by serial microdilution assay as previously reported 11) . Serial two-fold dilutions of each disinfectant were made in wells of a 96-well microplate containing BHI broth, and test samples (50 µL; concentrations ranged from 0.000095 to 25% of the original solution) were prepared.…”
Section: Mic and Mbc Measurementsmentioning
confidence: 99%